MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA BOJONG JENGKOL, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Rully Trihantana; Ria Kusumaningrum; Setiawan Bima Prasetya (SAHID DEVELOPMENT JOURNAL, 2022)
Informal Islamic economic and business education is a process of economic education that occurs indirectly in the family environment such as education for financial transactions. The aim of Islamic economics and business education is none other than to increase public knowledge in managing their finances. The community service activities carried out from July to August 2021 and located in Bojong Jengkol Village, Ciampea District, Bogor Regency, aim to provide a deeper understanding of Islamic economics and business education by providing materials such as habituation to diligent saving, habituation to manage money in meeting primary and secondary needs, habituation to be selective in purchasing goods and use of services, habituation to be a smart consumer, habituation to compare between price and quality, habituation to develop entrepreneurial spirit. The community is enthusiastic about this community service activity, and they have a better understanding of it to apply in their daily lives.